Morphology of C6 Glioma Cells on a Water-Repellent Fractal Alkyl Ketene Dimer Surface - Hu, Wei-wei; Yan, Hu; Birukawa, Naoko; Abe, Masashi; Ito, Etsuro; Tsujii, Kaoru; Chen, Zhong; Urano, Akihisa (Current Nanoscience, 2008)
In many in vitro cultures, cells may change their morphology, probably caused by adherence to the surface of the culture dish. Since a fractal alkyl ketene dimer (AKD) surface provides super water-repellency with a contact angle of 174° , we considered that it might provide an improved surface environment for the growth and differentiation of cells by preventing intimate adhesion. C6 glioma cells which were selected to test the effects of the fractal surface, were cultured on a conventional surface, a smooth AKD surface or a fractal AKD surface. On the conventional and smooth AKD surfaces, cells developed bipolar or multipolar shapes with enlarged cell bodies and neurite-like processes. In contrast, cells cultured on the fractal AKD surface presented fine filopodium-like processes like protoplasmic astrocytes in vivo, and higher morphological complexity was revealed by fractal analysis. Reconstruction of three-dimensional shape indicated that cells on the fractal surface were globular, whereas those on the conventional surface were rather flat. Our results suggest that C6 glioma cells on a fractal AKD surface show features of natural astrocytes with their elaborate morphology. The fractal surface thus may provide a new and natural culture environment for experimental assessment of glial structure and function.
Keywords: cytoskeleton